Inequalities in health system responsiveness among asylum seekers and refugees: A population-based, cross-sectional study in Germany - Louise Biddle; Judith Wenner; Kayvan Bozorgmehr (Public Library of Science (PLoS), 2022)
Global migration has sparked renewed interest in Universal Health Coverage in high-income countries. However, quality of care has received little attention. This study uses the concept of responsiveness to study quality of care for asylum seekers and refugees (ASR) in Germany and identify inequalities among this group. We report results from a population-based, cross-sectional health monitoring survey in Germany's third-largest federal state using random sampling methods. Established instruments were used to measure responsiveness, health status and socio-demographic factors. Data were weighted and adjusted logistic regression models applied to identify inequalities related to health status, structural and socio-demographic factors. N = 344 survey participants were included in the analysis (response rate 39.2%). Combined responsiveness was 77% (95%CI: 68%; 83%) but varied between domains. Responsiveness was poor for individuals with symptoms of anxiety (OR 0.35, 95%CI 0.13,0.99), longstanding illness (OR:0.42, 95%CI:0.17,1.06) and diminished health-related quality of life (OR:0.24, 95%CI:0.06,0.95). Individuals from Southern Asia (OR: 0.24, 95%CI: 0.07,0.86) and young participants (OR:0.31, 95%CI:0.12,0.82) also reported less responsive care. Unique patterns of explanatory factors were identified within each responsiveness domain. We found important differences in responsiveness related to health, socio-demographic and structural factors, both in combined responsiveness and in individual domains. Inequalities related to health status factors are particularly concerning given the potential implications for equity of access. Future research should explore responsiveness for different sectors, include individuals who have not utilised healthcare and allow for the adjustment of differential expectations of care between population groups.